(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the analysis of the problem of adaptation of today’s first-graders to study at school. The article gives a psychological description of adaptation of first-graders to study, the specifics of adaptation of first-graders to study under conditions of the program "On the Wings of Success". The results of the experimental study of the features of the study of the emotional value relation of first-graders to classmates, schools, and educational activities in the class as indicators of their adaptation to study have been illustrated in the article. The results of the comparative analysis of the diagnostics results of the emotional experience of social contacts by the first-graders trained under the program "On the wings of success" and under conditions of traditional education have been presented.